2022
DOI: 10.1002/ajpa.24585
|View full text |Cite
|
Sign up to set email alerts
|

Childhood stress and developmental instability: Comparing microscopic enamel defects and cranial fluctuating asymmetry in a colonial Mexican sample

Abstract: Objectives Recent tests of the relationship between enamel defects, an indicator of early life stress, and fluctuating asymmetry (FA), a measure of cumulative developmental instability, have produced equivocal results. This may be because they use methods that underestimate the number of defects. We reinvestigate this relationship using high‐resolution microscopy images of tooth surfaces. Further, we test the hypothesis that developmental stresses during the earliest period of tooth development have a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…To this end, the impact of developmental instabilities on FA is thought to be magnified during ontogeny, such that the impact of early-life adversity may contribute more strongly to FA than hardship experienced when the skeleton has already been formed (Gluckman & Hanson, 2006;Hallgrímsson, 1999). This theory is substantiated by recent work into the human cranium, which highlights a window of vulnerability to developmental instability occurring between 1 and 5.5 years of age, with a uniquely sensitive time between 4 and 5.5 years (Moes et al, 2022).…”
Section: Other Potential Contributors To Fluctuating Asymmetrymentioning
confidence: 97%
“…To this end, the impact of developmental instabilities on FA is thought to be magnified during ontogeny, such that the impact of early-life adversity may contribute more strongly to FA than hardship experienced when the skeleton has already been formed (Gluckman & Hanson, 2006;Hallgrímsson, 1999). This theory is substantiated by recent work into the human cranium, which highlights a window of vulnerability to developmental instability occurring between 1 and 5.5 years of age, with a uniquely sensitive time between 4 and 5.5 years (Moes et al, 2022).…”
Section: Other Potential Contributors To Fluctuating Asymmetrymentioning
confidence: 97%
“…Similarly, some scholars have suggested that other social categories, such as sex (as a proxy for gender), could play a critical role, causing individuals who experience sex-or gender-based discrimination or stress to develop higher levels of FA compared to their peers who are buffered by more privileged social positions (Jung et al, 2016). A final note about seemingly conflicting findings in bioarchaeological research of craniofacial FA YAUSSY comes from Moes et al (2022), who suggest that the timing and duration of developmental stress events may play a role in the patterns of FA observed among adults. Specifically, Moes et al (2022) find that enamel defects indicating developmental stress events between 4 and 5.5 years of age were associated with higher levels of FA compared to enamel defects signaling stress during earlier developmental windows.…”
Section: Fluctuating Asymmetrymentioning
confidence: 99%
“…A final note about seemingly conflicting findings in bioarchaeological research of craniofacial FA YAUSSY comes from Moes et al (2022), who suggest that the timing and duration of developmental stress events may play a role in the patterns of FA observed among adults. Specifically, Moes et al (2022) find that enamel defects indicating developmental stress events between 4 and 5.5 years of age were associated with higher levels of FA compared to enamel defects signaling stress during earlier developmental windows.…”
Section: Fluctuating Asymmetrymentioning
confidence: 99%
See 2 more Smart Citations